2007 International Conference on Wireless Communications, Networking and Mobile Computing 2007
DOI: 10.1109/wicom.2007.626
|View full text |Cite
|
Sign up to set email alerts
|

An Event Aware Anycast Rooting Protocol in Wireless Sensor Networks

Abstract: Anycast is a mechanism that sends the data to the nearest node, which have the same anycast address. For those event-driven wireless sensor network application, anycast mechanism is effective. Event Aware Anycast (EAA) is proposed, which uses the complete or part data fusion according to the relativity of the data. The EAA algorithm preferably solve the construction of the routing in WSNs driven by events, decrease the spending of the route re-construction because of the moving of the Sensor nodes, and it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Zhou et al [12] proposed the Occasion Aware Anycast, which utilizes the entire or part information combination as indicated by the relativity of the information. The EAA calculations ideally fathom the development of the direction in WSNs driven by occasions and diminish the spending of the course redevelopment in light of the moving of the sensor hubs, and it remains the occasion area data amid the information combination.…”
Section: Related Workmentioning
confidence: 99%
“…Zhou et al [12] proposed the Occasion Aware Anycast, which utilizes the entire or part information combination as indicated by the relativity of the information. The EAA calculations ideally fathom the development of the direction in WSNs driven by occasions and diminish the spending of the course redevelopment in light of the moving of the sensor hubs, and it remains the occasion area data amid the information combination.…”
Section: Related Workmentioning
confidence: 99%
“…References [14][15][16][17][18][19] introduced the (m) anycast communication model into the data-centric WSN to improve the network service performance. The research results showed that the introduction of the (m) anycast communication model enhanced the cooperation ability of sensor nodes, shortened the delay time of data transmission, and effectively saved network resources.…”
Section: Related Workmentioning
confidence: 99%
“…The research results showed that the introduction of the (m) anycast communication model enhanced the cooperation ability of sensor nodes, shortened the delay time of data transmission, and effectively saved network resources. However, the (m) anycast communication models in [14][15][16][17][18][19] were only for the datacentric WSN, and they were implemented based on the datacentric routing mechanism of WSN, so it was difficult to apply the research results into the address-centric 6LoWPAN. Therefore, it needs to introduce an (m) anycast model based on the address-centric mechanism into 6LoWPAN so that the data-centric tasks can be implemented efficiently in 6LoWPAN.…”
Section: Related Workmentioning
confidence: 99%